Outdoor education program participation on UiTM students' leadership practices / Siti Fadhilah Abdul Hamid - Abdul Hamid, Siti Fadhilah (2014)
The phenomenon of unemployment due to lack of communication and leadership skills has become one of the main issues among graduates in Malaysia. The rapid changes of knowledge and technology require students to equip themselves with extra skills needed by global workplace to demonstrate the combination of soft skills together with a good degree. Thus, higher education is working harder to make sure the students are equipped with leadership skill. However, there are lacking of information, assessment and unclear program contents that can bring positive outcome toward the development of leadership skill. This study aims to examine an outdoor education program as one of the useful programs that higher education could use to identify the leadership practices among the students. It is done by comparing students who have participated in outdoor education program and those who did not participate using convenience sampling. A total of 106 students from the Faculty of Sport Science and Recreation UiTM were involved in this study. The data was collected by using Students Leadership Practices Inventory questionnaire to measure five leadership practices namely as ‘Model the Way’, ‘Inspire a Shared Vision’, Challenge the Process’, ‘Enable Others to Act’ and ‘Encourage the Heart’. Independent sample t-test was used in order to identify a significant difference of five leadership practices between the two groups of students. The results showed that there were significant differences in all five leadership practices among the students who have participated in outdoor education program. Finally, this study has proposed that outdoor education program is one of the effective activities that could be offered to all students by higher education to equip them with leadership skills required for future employability.